On the emergence of toyboys: Equilibrium matching with ageing and uncertain careers - Melvyn G. Coles; Marco Francesconi (Institute for the Study of Labor (IZA), 2007)
Toyboy marriages (where the female partner is at least 5 years older than her male partner) have grown threefold since the 1970s in the United States and Britain. This paper examines this phenomenon using an equilibrium search framework in which becoming successful in the labour market takes time and fitness decays with age. Our framework hinges on contract incompleteness in the marriage market and the assumption that the marginal gain to marrying someone rich is greatest for someone poor. With this structure we can explain why successful (older) types might marry fitter (younger) and less successful types. We show that toyboy marriages arise in equilibrium only when men and women have comparable labour market opportunities. U.S. and British data confirm this indicating that the probability that a woman is married to a toyboy increases by about 45 percent if, relative to her partner's, she is more educated and in a better paid job.
urn:nbn:de:101:1-2008042299
Keywords: 330; Ehe; Altersgruppe; Frauenerwerbstätigkeit; Erwerbsverlauf; Arbeitsmarktdiskriminierung; USA; Großbritannien